2015
DOI: 10.3109/14764172.2015.1007064
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study for the treatment of acne vulgaris using high-intensity 414 nm solid state diode arrays

Abstract: The treatment of acne vulgaris poses a challenge to the dermatologist, and the disease causes emotional anxiety for the patient. The treatment of acne vulgaris may be well-suited to home-use applications, where sufferers may be too embarrassed to seek medical treatment. This randomized controlled study is designed to quantify the effectiveness of using a blue light device in a therapy combined with proprietary creams, in the investigation of a self-treatment regimen. A total of 41 adults with mild-to-moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…However, phototherapy using blue light has been shown to significantly reduce inflamed acne lesions when irradiated for over eight treatment sessions in 30 subjects with mild to moderate facial acne . Recently, a randomized controlled study by Ash et al . reported that blue light therapy at 414 nm significantly reduces inflammatory acne lesions by 50.02% at the 12‐week assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phototherapy using blue light has been shown to significantly reduce inflamed acne lesions when irradiated for over eight treatment sessions in 30 subjects with mild to moderate facial acne . Recently, a randomized controlled study by Ash et al . reported that blue light therapy at 414 nm significantly reduces inflammatory acne lesions by 50.02% at the 12‐week assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, phototherapy using blue light has been shown to significantly reduce inflamed acne lesions when irradiated for over eight treatment sessions in 30 subjects with mild to moderate facial acne. 48 Recently, a randomized controlled study by Ash et al 49 reported that blue light therapy at 414 nm significantly reduces inflammatory acne lesions by 50.02% at the 12-week assessment. In our previous multicenter, randomized, split-face study, we demonstrated that the use of chromophore-assisted blue light phototherapy twice weekly for 6 weeks was efficacious, resulting in a reduction of at least 2 grades in the IGA scale in a statistically significant number of treated hemifaces of patients at 12 weeks (51.7% compared to 18.0% of the untreated hemifaces).…”
Section: Discussionmentioning
confidence: 99%
“…3,15,21,27 Three trials combined the light intervention with topical treatments as adjuncts. 21,24,25 Five trials compared the blue light with no treatment or a sham device. Other comparators included topical cleansers (such as benzoyl peroxide), other topical agents such as salicylic acid to promote desquamation, or retinol.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…26 Two trials reported the number of AEs for the trial overall rather than by treatment group 3,16 ; few AEs were reported, and 4 trials reported narratively that the treatment had no side effects or was side-effect free. 15,18,24,25…”
Section: Week 10-12mentioning
confidence: 99%
“…Anti-inlammatory efect on keratinocyte occurs by reducing IL-1 and ICAM markers. As stated before, when porphyrin produced by P. acnes absorbs light, it produces free oxygen radicals being toxic for the bacteria [13,14].…”
Section: Narrowband Blue Lightmentioning
confidence: 99%